Modeling of Nuclear Waste Forms: State-of-the-Art and Perspectives. (2020) - Kowalski, Piotr. M.; Lange, Steve; Deissmann, Guido; Sun, Mengli; Kvashnina, Kristina O.; Baker, Robert; Kegler, Philip; Murphy, Gabriel; Bosbach, Dirk
ABSTRACT: Computational modeling is an important aspect of the research on nuclear waste materials. In particular, atomistic simulations, when used complementary to experimental efforts, contribute to the scientific basis of safety case for nuclear waste repositories. Here we discuss the state-of-the-art and perspectives of atomistic modeling for nuclear waste management on a few cases of successful synergy of atomistic simulations and experiments. In particular, we discuss here: (1) the potential of atomistic simulations to investigate the uranium oxidation state in mixed-valence uranium oxides and (2) the ability of cementitious barrier materials to retain radionuclides such as 226 Ra and 90 Sr, and of studtite/metastudtite secondary peroxide phases to incorporate actinides such as Np and Am. The new contribution we make here is the computation of the incorporation of Sr by C-S-H (calcium silicate hydrate) phases.